The mutation of TBC1D24 associated with epilepsy: About 3 cases - Mehdaoui , A; Khabbache , K; Bousgheiri, F; Najdi, A; Eddaoudi, S; El Boussaadni, Y; Oulmaati, A; Abdallah, Pr oulmaati (International Journal of Health Sciences, 2023)
Purpose : The aim of our work is to study the clinical, electrical, imaging and evolutionary profile of epilepsy caused by mutation of the TBC1D24 gene in our patients and to emphasize the interest of genetic counseling. Methodology : This is a qualitative observational study about 3 cases, highlighting the clinical, electrical, and evolutionary characteristics of the disease. Findings : In this study we report the clinical history of three patients from two families, hospitalized at the Mohamed V hospital in Tangier, during the year 2022, having in common a first degree consanguinity, a severe epilepsy, pharmaco-resistant, with a very early onset during the first months of life, with several hospitalizations for epileptic seizures, the repercussion on psychomotor development, and schooling was noted with the three children, the genetic study confirmed the presence of mutation of the TBC1D24 gene. Unique contribution to theory, practice and policy: The cases reported in the literature are not numerous (1) (2) (3). Balestrini et al (1), reported 48 cases, followed for epilepsy related to the mutation of this gene, with a great clinical heterogeneity, and an age of onset in early childhood. The correlation between the TBC1D24 gene and epilepsy was known for the first time in 2010,it represents a great clinical heterogeneity, ranging from simple epileptic seizure with good cognitive and intellectual development and complete control of the disease, to severe epileptic encephalopathy, so the mutation of this gene can be associated with brain malformations and can be found in several syndromes including DOORS syndrome (which associates deafness, intellectual disability, seizures, onycho-dystrophy, osteo-dystrophy). This mutation is also described in non-syndromic deafness and in people suffering from various forms of epilepsy, including familial infantile myoclonic epilepsy, progressive myoclonic epilepsy, focal migrating epilepsy and writer's stress-induced paroxysmal rolandic-dystonic epilepsy syndrome. A panel of genes were searched in particular clinical situations when there are severe epilepsies, consanguinity, or similar family cases, with or without other associated damaged organ, thus the screening of the TBC1D24 mutation is indicated in a wide variety of epilepsies.